How to culturally adapt the pulmonary rehabilitation programme for people living with COPD in Sri Lanka: a qualitative study - Sally J Singh; Andy Barton; Amitha Fernando; Mark Orme; Chamilya Perera; Akila Jayamaha; Thamara Dilhani Amarasekara; Zainab Yusuf; Amy Barradell; James Manifield; Ravini Karunathilake; Savithri Wasundara Wimalasekera (BMJ Open Respiratory Research, 2025)
Background Pulmonary rehabilitation (PR) is a low-cost, high-impact intervention for people living with chronic obstructive pulmonary disease (COPD). Despite the high prevalence of COPD, there are currently very limited facilities to provide PR in Sri Lanka. The views of people living with COPD, their caregivers and relevant healthcare professionals (HCPs) are essential to develop culturally appropriate PR, acceptable in a Sri Lankan setting.Objectives We aimed to explore the lived experiences of key stakeholders on the development and implementation of culturally appropriate PR in Sri Lanka.Methodology A qualitative study was conducted at the Central Chest Clinic (CCC), Sri Lanka. Focus group discussions (FGDs) and semistructured interviews (SSIs) were conducted with the three populations: people living with COPD, their caregivers and relevant HCPs. After audio recording, transcribing and translating, the data were analysed using thematic analysis.Results Three FGDs comprising 11 adults with COPD (9 males, age range 39–83 years), three FGDs comprising five family caregivers (three females), three FGDs comprising 14 nurses and 12 SSIs with doctors and physiotherapists were conducted, representing diverse ethnic groups. Two overarching themes were generated: ‘PR adaptations’ and ‘Barriers to PR implementation and adherence’. Within ‘PR adaptations’, four subthemes were generated: the educational component of PR, nutritional support, psychological support and the use of music during PR sessions. Under ‘Barriers to PR implementation and adherence’, three subthemes were generated: barriers and issues in participating, need for better medical facilities and difficulty in conducting exercises.Conclusion Culturally tailoring PR for people living with COPD in Sri Lanka should include the integration of singing, music and nutritional support, as it may enhance acceptability. Barriers, including a lack of resources to deliver PR, difficulties encountered by patients attending PR sessions and perceived difficulties in performing standardised PR exercises, need to be addressed when developing a culturally appropriate programme in Sri Lanka.